Prognostic Value of Left Atrial Strain in Heart Failure: A Systematic Review and Meta-Analysis - Jia, Fuwei; Chen, Antian; Zhang, Dingding; Fang, Ligang; Chen, Wei (Frontiers in Cardiovascular Medicine, 2022)
Background: Heart failure (HF) is a global health problem with high morbidity and mortality. Recently, the association between peak atrial longitudinal strain (PALS) and clinical outcomes of HF has gained increasing attention. Our aim was to systematically assess the prognostic value of PALS for adverse events in HF. Methods: PubMed, Embase and Scopus databases were systematically searched inception to April 30, 2022. Studies in which PALS was assessed to predict adverse outcomes in adult patients with HF were included. Study selection, quality assessment and data extraction were performed independently by two authors. The primary endpoint was all-cause death and cardiac hospitalization. Results: Among 7787 patients in 17 included studies, 3029 (38.9%) experienced the primary endpoint. Patients with events had lower PALS than those without events (weighted mean difference 6.17%, 95% CI 3.09-9.26, p < 0.001). Each unit increment of PALS was independently associated with decreased risk for the primary endpoint (HR 0.96, 95% CI 0.94-0.98, p < 0.001). The addition of PALS significantly improved the predictive power of conventional risk models (NRI 0.22, 95%CI 0.06-0.39, p = 0.008). Conclusions: PALS was an independent predictor for all-cause mortality and cardiac hospitalization in patients with HF, highlighting the clinical importance of left atrial deformation in the prognosis of HF.